Services and Performance of the Indian Economy Analysis and Policy Options - Benz, Sebastian (OECD Trade Policy Papers, 2017)
This paper highlights India's unique services export led growth path. Observing that Indian business services have helped manufacturers all over the world to become more efficient and productive, it raises the question how Indian business services can do the same for local manufacturers and thus support the Make in India initiative. The paper also explores the potential for broadening the export base in services. The services sector that appears to have the largest prospect for unleashing the potential of both manufacturing and knowledge intensive business services is the telecommunications sector, particularly broadband internet services. In addition reforms in the distribution sector that enable multi-channel wholesale and retailing could facilitate the development of marketing channels for SME manufacturers both across the vast Indian market and abroad. Reforms in the logistics sector would further improve the competitiveness of local manufacturers producing time-sensitive goods including inputs to global value chains. Finally, competitiveness in knowledge-intensive services is obtained through knowledge sharing across borders. A prerequisite for broadening the export base in these sectors is openness to foreign professionals. The set of proposed recommendations emerging from this analysis underlines the importance of streamlining sector-level regulatory frameworks in all sectors to encourage foreign entry and competition, and the role that cross-cutting improvements in the trade and business environment would play to render services providers as well as down-stream manufacturers more competitive